Approaches to the Middle Paleolithic rockshelter and cave research in Croatia - Karavanić, Ivor; Vukosavljević, Nikola; Šošić, Rajna Mihelić, Sanjin (2007)
This paper presents the research history of the Middle Paleolithic cave sites in Croatia traced on the basis of investigations of three sites: Krapina, Vindija (both in northwestern Croatia) and Mujina Pećina (southern Croatia). The first Middle Paleolithic site to be discovered was Krapina. It was excavated by Dragutin Gorjanović-Kramberger. His excavation methodology was very sophisticated at the time, and included stratigraphic excavation and notes on the horizontal distribution of finds in certain parts of the site. The Vindija cave yielded important finds of late Neanderthals associated with Mousterian industry (level G3) and possibly with Upper Paleolithic bone industry in level G1. In southern Croatia, the only systematically excavated Middle Paleolithic site is Mujina Pećina. The Mousterian people in both regions of Croatia (northwestern and southern) successfully adjusted the production of their tools to various types of the most easily accessible raw materials, and they were successful predators.
Projekt MZOS
ENG